The criminalisation of unaccompanied migrant minors : voices from the detention processes in Greece - Papadopoulos, Ioannis (Bristol University Press, 2023)
Greece is a key EU entry country for unaccompanied migrant minors seeking safety but such children are frequently criminalised through detention processes. Giving voice to migrant children throughout, Papadopoulos promotes child-friendly practices and the safeguarding of fundamental rights.